The Internet Use for Health Information Seeking among Ghanaian University Students: A Cross-Sectional Study - Asibey, B.O.; Agyemang, S.; Dankwah, A.B. (International Journal of Telemedicine and Applications, 2017)
The aim of the study was to investigate university students' use of the Internet for health purpose in the Ghanaian context. The study employed a quantitative cross-sectional design. A total of 650 out of 740 students selected from 3 different universities participated, giving a response rate of 87.7% (650/740). Data were obtained using questionnaires and frequency and percentages were used to analyze data. The results show that university students are active users of the Internet as 78.3% (509/650) used Internet daily and 67.7% (440/650) use Internet for health purposes, for reasons including availability and ease of accessing information, privacy, confidentiality, and affordability. Use of Internet was constrained by unreliable and slow connection, high cost of Internet, and unreliable power supply. Also, 72.4% (315/435) used the online health information obtained as a basis for lifestyle change and only 39.5% (170/430) consulted health professionals after obtaining online information. The study concludes that students use Internet to seek online health support. The use of Internet to communicate with young people in relation to their health must therefore be explored. There is the need to be aware of online safety issues for young adults, including the need to provide information on privacy options. © 2017 Benedict Osei Asibey et al.
Keywords: Internet Use; Internet; Health Information; Ghana; University Students